Practicing the art of Telepuk: an experimental study with media and technique / Noor Hana Mohd Jabar - Mohd Jabar, Noor Hana (2013)
In today’s technological era, we can see the rise of interestingly new and creative creations and inventions that help promote Malaysia to the rest of the world including the art of textile. Malaysia is a country with own unique textile identity. Due to the impact of globalization and modernization in Malaysia, traditional Malay art is worried might eventually becoming irrelevant and unattractive to most Malaysian. ‘Telepuk’ is one of the examples of traditional heritage that’s fading from Malay culture. This art form is facing extinction, unless necessary measures are taken to preserve and change traditional techniques and give it a fresh, contemporary feel. The creation and usage of textile can be the perfect link to create, express and maintain a culture as it shows spirituality, symbolism and tradition. This is where the role of education can help instill and educate young generations especially students to love and appreciate art works created by its own people rather than others. Hence, the researcher uses art-based research study to give emphasis on the suitable media and technique for practising the art of telepuk in visual arts lesson. This study is an art-based research that focuses on examining the artistic process. The assimilation of both the stencil and resist techniques can indefinitely inject a newer and contemporary method in producing the ‘telepuk’ textile.